PENGARUH E-WOM TERHADAP PURCHASE DECISION PADA AYAM BETUTU BU LINA GILIMANUK, BALI - Jocelyn Nie; Ferawati Angelita; Yolanda Febryna; Amelia; Vanesya Beatrix; Christopher Chendra; Jerry Wijaya (Universitas Triatma Mulya, 2023)
E-WOM, as one of the marketing techniques developed from the old marketing technique namely Word-of-mouth by adapting digital technology, becomes one of the effective marketing techniques. The purpose of this study is to analyze the effect of e-WOM and customer satisfaction towards purchase decision. The object used is